2012
DOI: 10.1371/journal.pone.0046090
|View full text |Cite
|
Sign up to set email alerts
|

miR-511 and miR-1297 Inhibit Human Lung Adenocarcinoma Cell Proliferation by Targeting Oncogene TRIB2

Abstract: microRNAs (miRNAs) are small noncoding RNAs that regulate genes and contribute to many kinds of human diseases, including cancer. Two miRNAs, miR-511 and miR-1297, were investigated for a possible role in adenocarcinoma based on predicted binding sites for the TRIB2 oncogene by microRNA analysis software, and the pcDNA-GFP-TRIB2–3′UTR vector was constructed to investigate the interaction between TRIB2 and miR-511/1297 in the adenocarcinoma cell line A549. Green fluorescent protein (GFP) expression was estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 33 publications
6
64
0
Order By: Relevance
“…Since the 1970s, celastrol has been identified to possess anti-inflammatory, anti-oxidative and tumor cell-inducing apoptotic properties. Furthermore, compared with other anticancer drugs, celastrol selectively targets tumor cells and causes no obvious damage to normal hematopoietic cells, the heart, liver, kidney or other organs (20)(21)(22). Therefore, celastrol is considered to be a relatively safe and effective anticancer drug.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1970s, celastrol has been identified to possess anti-inflammatory, anti-oxidative and tumor cell-inducing apoptotic properties. Furthermore, compared with other anticancer drugs, celastrol selectively targets tumor cells and causes no obvious damage to normal hematopoietic cells, the heart, liver, kidney or other organs (20)(21)(22). Therefore, celastrol is considered to be a relatively safe and effective anticancer drug.…”
Section: Discussionmentioning
confidence: 99%
“…Various miRNAs have been regarded as the biomarkers and therapeutic targets for CC patients (11). miR-1297, a novel cancer-related microRNA, has been found to play vital role in the pathogenesis of human cancer (12,13). miR-1297 promoted cell proliferation via downregulation of the tumor-suppressor gene retinoblastoma (RB) 1 in liver cancer (14), while Liu et al reported that miR-1297 played a crucial role in promoting cell apoptosis and inhibiting proliferation by targeting EZH2 in hepatocellular carcinoma (15).…”
Section: Introductionmentioning
confidence: 99%
“…To date, no other studies have reported an association between miR-1297 and liver cancer. However, miR-1297 has been reported to regulate the carcinogenesis of colorectal cancer (19), lung adenocarcinoma (20) and laryngeal squamous cell carcinoma (21). In addition, its predicted target gene, RB1, is a negative regulator of the cell cycle and a tumor-suppressor gene (22).…”
Section: Discussionmentioning
confidence: 99%